Effects of the alang-alang (Imperata cylindrica) cutting practices to the gall growth. Issue 1 (March 2020) - Syah, R F; Hidayat, P
Abstract: Alang-alang is an invasive weed species that can grow out of control and harm other plants. The weed control methods commonly applied are burning, cutting, and spraying with herbicides. There is an insect causing alang-alang gall found in Java, namely Orseolia javanica Kieffer & van Leeuwen-Reijnvaan (Diptera: Cecidomyiidae) or known as the alang–alang gall midge. This study was aimed at determining the effects of the alang–alang cutting practice on rice field bunds to the growth of alang–alang galls. The study was done in Cianjur District, West Java. There were several steps done in this study including the preparation of field sites, daily observation of the gall growth, and observation on the duration of the gall midge for emerging. The length of the alang-alang gall on the uncut alang-alang was significantly higher than on the cut alang-alang, while the diameter of the galls was not significantly different. The difference in the length of the galls is believed was due to the different of light exposures. The duration of the emerging time for the alang-alang gall midge was shorter on the cut than the uncut alang-alang which was might be caused by changes in micro climate such as the more sunlight exposures and higher temperature on the habitat. This study suggests that the alangalang cutting practice can shorten the life cycle of the alang–alang gall midge and might have an impact on the biological control effectiveness.